The Little Database: A Poetics of Media Formats - Snelson, Daniel Scott (University of Minnesota Press, 2025)
A poetics for reading the everyday objects that populate a hard drive Bespoke online archives like PennSound and Eclipse host an astounding array of “old media” artifacts, posing a handcrafted counterpoint to the immense databases aggregated by digital titans like Google and Facebook. In The Little Database, Daniel Scott Snelson argues for the significance of these comparatively “small” collections, exploring how digital archives dramatically transform the artifacts they host and how they might help us better understand our own private collections in turn. Examining curated collections such as Textz, UbuWeb, and the Electronic Poetry Center, Snelson explores media-specific works by poets and artists, including William Carlos Williams, Tracie Morris, bill bissett, Nam June Paik, and Vicki Bennett. He develops creative tools and contingent methods for reading cultural data, whether found on the internet or in our own collections of TXT, JPG, MP3, and MOV artifacts, presenting case studies to show how these objects have come to find revised meaning in their digital contexts. Along the way, experimental poetic interludes give readers practical entry points into the creative practice of producing new meanings in any given little database. Inventive and interdisciplinary, The Little Database grapples with the digitized afterlives of cultural objects, showing how the past is continually reconfigured to shape the present. It invites readers to find playful and personal means for unpacking their own data collections, in the process discovering idiosyncratic ways to explore and connect with digital archives. Retail e-book files for this title are screen-reader friendly with images accompanied by short alt text and/or extended descriptions.